2019
DOI: 10.1111/jcmm.14231
|View full text |Cite
|
Sign up to set email alerts
|

Predicting overall survival of patients with hepatocellular carcinoma using a three‐category method based on DNA methylation and machine learning

Abstract: Hepatocellular carcinoma (HCC) is closely associated with abnormal DNA methylation. In this study, we analyzed 450K methylation chip data from 377 HCC samples and 50 adjacent normal samples in the TCGA database. We screened 47,099 differentially methylated sites using Cox regression as well as SVM‐RFE and FW‐SVM algorithms, and constructed a model using three risk categories to predict the overall survival based on 134 methylation sites. The model showed a 10‐fold cross‐validation score of 0.95 and satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…It is at least in part due to this ability to make 'evidence-based' decisions that, as AI-health research has shown, AI techniques can considerably augment or surpass human capabilities when it comes to tasks including: (1) analysis of risk factors ( prediction of outcome and/or likelihood of survival (Dong et al, 2019;Popkes et al, 2019;Topuz, Zengul, Dag, Almehmi, & Yildirim, 2018); and (7) analysing electronic health records (Shickel, Tighe, Bihorac, & Rashidi, 2018). These capabilities should not be underestimated, particularly as AI-Health solutions can operate at scale, diagnosing or predicting outcomes for multiple people at once -something that an HCP could never do.…”
Section: Epistemic Concerns: Inconclusive Inscrutable and Misguidedmentioning
confidence: 99%
“…It is at least in part due to this ability to make 'evidence-based' decisions that, as AI-health research has shown, AI techniques can considerably augment or surpass human capabilities when it comes to tasks including: (1) analysis of risk factors ( prediction of outcome and/or likelihood of survival (Dong et al, 2019;Popkes et al, 2019;Topuz, Zengul, Dag, Almehmi, & Yildirim, 2018); and (7) analysing electronic health records (Shickel, Tighe, Bihorac, & Rashidi, 2018). These capabilities should not be underestimated, particularly as AI-Health solutions can operate at scale, diagnosing or predicting outcomes for multiple people at once -something that an HCP could never do.…”
Section: Epistemic Concerns: Inconclusive Inscrutable and Misguidedmentioning
confidence: 99%
“…Lee et al proposed a data-driven construction method for survival risk-gene networks as well as a survival risk prediction method using the network structure [8]. Dong et al used machine learning to analyze DNA methylation data to build a model with three risk categories for predicting survival of hepatocellular carcinoma patients [9]. Prognostic risk model was constructed in glioblastoma multiform based on mRNA/microRNA/long non-coding RNA analysis using random survival forest method [10].…”
Section: Discussionmentioning
confidence: 99%
“…Cox regression, SVM‐RFE and FW‐SVM algorithms were used to screen out differentially methylated sites. And this study was performed based on TCGA (training set) and GSE77269 (validation set), the sample size of our study was limited, and large‐scale cohort studies are needed . In this study, we constructed a signature involving only 10 lncRNAs.…”
Section: Discussionmentioning
confidence: 99%